Relevance of Key Performance Indicators and Islamic Higher Educations Reputation - Tolkah Tolkah; Heny Yuningrum; Rahman El Junusi; Ferry Khusnul Mubarok (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2022)
The university ranking is an achievement indicator based on reputation, especially global reputation. The objectives of this study are (1) To determine the relevance of Key Performance Indicators (KPI) and PTKINs’ reputation based on SMS and Webometrics ranking; (2) To find out the correlation between KPI and PTKINs’ Reputation. This study uses mixed methods or integration of quantitative and qualitative research. The research objects were 17 PTKINs. For the analysis technique, it uses person correlation and explorative analysis. The results showed that of 51 KPI criteria, only one was relevant to the reputation of PTKINs based on the SMS ranking. In contrast, there are 13 KPI criteria that fit PTKINs' reputation based on Webometrics ranking. KPI does not correlate with PTKINs’ reputation based on SMS ranking, while KPI correlates with PTKINs’ reputation based on Webometrics ranking. For this reason, a policy is needed to synchronize KPI with WCU standards that have been recognized globally. While the implementation of ranking based on SMS needs to be reviewed because it does not reflect PTKINs' reputation.